The reduction of chemical inputs by ultra-precise smart spot sprayer technology maximizes crop potential by lowering phytotoxicity - Anne, Pauline; Gasser, Simon; Göttl, Markus; Tanner, Steve (Frontiers in Environmental Economics, 2024)
Weeding is at the heart of agriculture. Nowadays, the use of herbicides is unavoidable in conventional agriculture. However, increasing ecological awareness, the need to reduce CO2 emissions, and the pursuit of sustainable food have driven industries and academics to explore new approaches to grow and protect crops. In this context, smart spot sprayers emerge as a highly innovative alternative to broadcast treatments that overuse pesticides and to mechanical weeding that is limited by restrictive application conditions. Using artificial intelligence (AI) for plant recognition and ultra-precise spraying technology, herbicides are applied directly to weeds with minimal overspray, reducing herbicides use by 90% compared to conventional methods. The narrow-targeted spray of the spot sprayers limits the contact of chemicals on the crop resulting in low phytotoxicity and preserving natural crop development while maximizing yield potential. Additionally, site-specific application artificially increases the selectivity of the chemical products, enabling the use of more concentrated mixtures. Also, the AI enables the selective application of non-selective molecules, supporting their use in established cultures. These characteristics open new opportunities for effective weed control, where the traditional solutions fall short. This publication demonstrates the potential of the ultra-precise smart spot sprayer ARA in weed management in onion and sugar beet crops. Even though this publication is not able to compare the overall performance of ARA with other smart spot sprayers on the market, it nevertheless indicates the potential of this technology in rendering weed management on farms more effective, sustainable, and labor-saving without compromising yield.